ANALISIS KONSEPTUAL ETIKA PROFESIONAL DAN IMPLEMENTASINYA TERHADAP ETOS KERJA GURU - Kamaliya Ramadhani; Azzani Izza Fahrezi; Salsabila Nadia Rahma Maulida; Muhlisin Muhlisin; Abul Mafaakhir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of professional ethics in fostering a work ethic among teachers amid the increasingly complex challenges of modern education. The decline in discipline and professional responsibility, as well as the weak commitment of some educators to the quality of learning, highlights the need to strengthen teachers’ professional ethics. This study aims to analyze the concept of teachers’ professional ethics and its implications for the development of a work ethic in the field of education. The study employs a qualitative approach using library research. Data were collected from various scholarly sources, including national journals, books, and educational regulations relevant to professional ethics and teachers’ work ethic. Data analysis was conducted through content analysis to identify conceptual relationships between professional ethics and teachers’ work ethic. The results of the study indicate that professional ethics have a significant influence on the formation of teachers’ work ethic, particularly in terms of responsibility, discipline, integrity, professional loyalty, and commitment to improving the quality of education. Teachers who possess a good understanding and application of professional ethics tend to demonstrate a higher work ethic in carrying out their educational duties. This study confirms that strengthening professional ethics must be an integral part of teacher competency development in order to continuously improve the quality of education.